#FutureGen – Lessons from a Small Country? - Jane Davidson (Revue Française de Civilisation Britannique)
In 2015 the government in Wales passed into law the Well-being of Future Generations (Wales) Act. This act is the first legislation in the world to enshrine the rights of future generations alongside current ones and requires Welsh Government ministers and the organisations they oversee to embed this commitment into everything they do. The creation of the Act was a brave and wonderful act by the Welsh Government and a vote of confidence by the Welsh legislature for a different, more sustainable future for Wales.Written by the Minister who proposed the Act, this article recounts what led up to it, examines why Wales was first to do it and then assesses whether it is working and what needs to happen next.